The individual micro-lending contract: Is it a better design than joint-liability? - Evidence from Georgia - Denitsa Vigenina; Alexander S. Kritikos (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2005)
We analyze the incentive mechanism of individual micro-lending contracts and we compare its key factors with those of joint-liability loan contracts. Using our data set, we firstly show that in the individual contract there are three elements, the demand for non-conventional collateral, a screening procedure which combines new with traditional elements, and dynamic incentives in combination with the termination threat in case of default, which ensure high repayment rates of up to 100%. We further show that the joint-liability approach may lead to similar repayment rates, however based on a different incentive system. We reveal that the target group which can be efficiently served by either one of the two mechanisms is different.
Keywords: 330; Mikrofinanzierung; Kreditgeschäft; Haftung; Ökonomischer Anreiz; Georgien